Adaptation Patterns and Yield Stability of Durum Wheat Landraces to Highland Cold Rainfed Areas of Iran. Issue 3 (1st May 2014) - Mohammadi, Reza; Haghparast, Reza; Sadeghzadeh, Behzad; Ahmadi, Hasan; Solimani, Kazem; Amri, Ahmed
ABSTRACT: Because of unpredictable conditions in Mediterranean environments, successful crop production requires improved adaptation and yield stability to mitigate major abiotic stresses such as drought and cold. In this study 380 durum wheat ( Triticum turgidum L.) landraces with worldwide origins and four checks were evaluated in four rainfed research stations for 3 yr (2008–2011). The main objective was to investigate yield stability and adaptation patterns of the landraces to highland rainfed cold regions of Iran, where drought and cold are limiting factors. The experimental design was an unreplicated trial at each environment. Best linear unbiased predictions (BLUPs) data were used to analyze landrace × environment interactions using multivariate statistical methods. Considerable variability in yield, adaptation, and stability was observed for the landraces, which could be exploited for crop improvement. The landrace and environment groups allowed characterization of origins on the basis of similar performance of landrace within particular environments. Grouping of environments was not repeatable among the years. Many of the durum landraces exhibited a high combination of yield and stability for both drought and cold stresses, comparable to cold‐ and/or drought‐tolerant checks. Most landraces originating from Europe and the United States could be considered as a genetic resource for specific adaptation, while the landraces from Asia may enhance genetic potential of yield stability. In conclusion, current durum wheat selection may lead to yield stability and specific adaptation, which provides opportunities for this collection to be useful for genetic improvement of both drought and cold tolerance in durum wheat.